Current state of mobile health apps in endourology: a review of mobile platforms in marketplaces and literature - Ali Talyshinskii; Guliev Bakhman; BM Zeeshan Hameed; Amelia Pietropaolo; Nithesh Naik; Bhaskar K Somani (Therapeutic Advances in Urology, 2023)
Several mobile healthcare (mHealth) apps are available in various marketplaces, but there is still concern about their accuracy, data safety, and regulation. The goal of this review was to critically analyze the mobile apps created for education, diagnosis, and medical and surgical treatment of patients with kidney stone disease (KSD), as well as to assess the level of data security, the contribution of physicians in their development and adherence to the Food and Drug Administration (FDA) and Medical Device Regulation (MDR) guidance. A comprehensive literature search was performed using PubMed (September 2022), in the Apple App Store and Google Play store using relevant keywords and inclusion criteria. Information was extracted for the name of the app, primary and additional functionalities, release and last update, number of downloads, number of marks and average rating, Android/iOS compatibility, initial and in-app payments, data safety statement, physician involvement statement, and FDA/MDR guidance. A total of 986 apps and 222 articles were reviewed, of which based on the inclusion, 83 apps were finally analyzed. The apps were allocated to six categories about their primary purpose: education ( n  = 8), fluid trackers ( n  = 54), food content description and calculators ( n  = 11), diagnosis ( n  = 3), pre- and intra-operative application ( n  = 4), and stent trackers ( n  = 2). Of these apps, the number of apps supported for Android, iOS, and both of them were 36, 23, and 23, respectively. Despite a wide range of apps available for KSD, the participation of doctors in their development, data security, and functionality remains insufficient. Further development of mHealth should be carried out properly under the supervision of urological associations involving patient support groups, and these apps must be regularly updated for their content and data security.